1976
DOI: 10.2136/sssaj1976.03615995004000010029x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Accretion in Developing Ceanothus Velutinus Stands

Abstract: Nodulation, N accretion, and above‐ground biomass production were investigated in Ceanothus velutinus (snowbrush) stands developing following wildfire and salvage logging in second growth ponderosa pine (Pinus ponderosa Laws) and logging and slash burning in old growth Douglas‐fir stands [Pseudotsuga menziesii (Mirb.) Franco]. In the pine site 82% of the Ceanothus plants were nodulated the first year, whereas in the fir site only 42% were nodulated. Above‐ground snow‐brush biomass production at the end of 10 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 0 publications
0
30
1
Order By: Relevance
“…bean plants) are important in TN storage. Many studies have found that nitrogen-fixing species can significantly increase soil N levels (Youngberg and Wollum 1976;Binkley 1992).…”
Section: Soil Chemical Characteristicsmentioning
confidence: 99%
“…bean plants) are important in TN storage. Many studies have found that nitrogen-fixing species can significantly increase soil N levels (Youngberg and Wollum 1976;Binkley 1992).…”
Section: Soil Chemical Characteristicsmentioning
confidence: 99%
“…Ceanothus velutinus is a pioneer species that invades after site such disturbances as fire in the eastern Sierran forests. Ceanothus is especially adapted to fire; heat treatment followed by cold stratification is required for seed germination (Zavitkovski and Newton 1968;Youngberg and Wollum 1976). Seeds lying dormant in forest litter for many years are activated by fire and winter weather, resulting in prolific germination in areas of wildfire, clearcut, or slash burn.…”
Section: Effects On Nutrient Cycling and Transportmentioning
confidence: 99%
“…On the other hand, in Little Valley, Nevada, patches of Ceanothus are common in a mosaic of 110-year-old Jeffrey pine forests. Furthermore, the benefits of Ceanothus on site fertility are clear; it replaces the N lost in fire and usually results in greater soil carbon and N contents than were there originally (Youngberg and Wollum 1976;Binkley et al 1982;. A prescribed low intensity burn in Pope Marsh resulted in increased nitrogen loading in spring runoff prior to the reestablishment of vegetation on the site (Norman 1997a).…”
Section: Effects On Nutrient Cycling and Transportmentioning
confidence: 99%
“…The authors speculated that removal of shrubs, particularly snowbrush ceanothus, abundant only within this exclosure, might alter rates of nutrient accumulation in soils, because Ceanothus spp. can fix atmospheric nitrogen (Youngberg andWollum 1976, Zavitkowski andNewton 1968). Tiedemann and Berndt (1972) found that herbivory reduced litter, which was 1.4 times greater inside than on the outside.…”
Section: Observed Effects Of Large Herbivores On Plants and Soils In mentioning
confidence: 99%